2016
DOI: 10.1007/s00423-016-1482-4
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards organ donation in German medical students

Abstract: The willingness to potentially act as organ donor was related to the pre-existent knowledge, trust, and fear. Access to information material did promote the decision towards organ donation in a group of previously undecided medical students. This advocates initiating information campaigns even in population groups with strong medical background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
3
16
1
1
Order By: Relevance
“…Women made up 65% of the total number of participants in our study, which is comparable with gender distributions in other works in university settings 10,15-17. Other studies that addressed the general population presented a more homogeneous distribution between genders 1,2,5,11-13,18,19.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Women made up 65% of the total number of participants in our study, which is comparable with gender distributions in other works in university settings 10,15-17. Other studies that addressed the general population presented a more homogeneous distribution between genders 1,2,5,11-13,18,19.…”
Section: Discussionsupporting
confidence: 88%
“…Studies assessing a sample's general knowledge about organ donation 1,2,11,13,14,16,17 have demonstrated misinformation on the same subjects as the control group in our study. Terbossen et al 17 showed that German medical students who did not carry a donor's card feared feeling pain during organ extraction procedures.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Access to relevant information may stimulate the unresolved minds to think in favour of donation. 6 Medical curriculum should highlight the importance of organ donation. Improving the attitudes of health care professionals could help to promote organ donation.…”
Section: Resultsmentioning
confidence: 99%